Determinación de las propiedades físico-químico del suelo de un lote de la comunidad Maca Chico mediante el uso de técnicas básicas del laboratorio de suelos año 2023 - Caisaguano Vega, Adriana Maribel (2024)
The present investigation was carried out in the Soil Laboratory of the Agronomy course, Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, with the objective of determining the physical and chemical properties of a potato (Solanum tuberosum) cultivation soil in the parish of San José de Poaló, Maca Chico community, Several methodologies were used that were adjusted to the soil laboratory, soil samples were taken and analyzed for structure, real density, bulk density, porosity, texture, pH, organic matter, nutrients and cation exchange capacity. For comparison and determination of the percentage of error, a soil sample was sent to the National Institute of Agricultural Research (INIAP). The results obtained from the physical-chemical characteristics of the soil in the laboratory of the Technical University of Cotopaxi (UTC), show a pH of 7.91 (alkaline), structure 1.123 mm (slightly stable), real density 2.13 g/cm3 (low), apparent density 1.33 g/cm3 (medium), porosity 38.48% (low), sandy loam soil, organic matter 2,26 % (medium), Na 96.5 ppm (low), K 83 ppm (medium), Ca 1884,5 ppm (high), NO3- 303 ppm (high), electrical conductivity 981 dSm-1 (medium) and cation exchange capacity 17, 83 meq/100g (medium), it is concluded that by means of the results of the soil analysis sent by the National Institute of Agricultural Research (INIAP) and the results obtained in the soil laboratory of the Technical University of Cotopaxi similar and reliable results were obtained, therefore a guide of basic physical-chemical practices is established to determine soil analysis in the laboratory of the Agronomy course of the Technical University of Cotopaxi.